Effect of organic manures and microbial inoculants on yield, root colonization and total bacterial population in turmeric (Curcuma longa L.) intercropped in arecanut (Areca catechu L.) garden - J K Hore, S S Roy (Journal of Spices and Aromatic Crops, 2011)
The effect of combination of organic manures namely, compost, vermicompost, phosphocompost and mustard cake and microbial inoculants namely, Azospirillum brasilense and arbuscular mycorrhiza (Glomus fasciculatum) were evaluated for the organic production of turmeric (Curcuma longa) (cv. Suguna) grown as intercrop in arecanut (Areca catechu) (cv. Mohitnagar) plantation at Mondouri (Nadia, West Bengal) A significant difference in rhizome yield was noticed when organic manure-microbial inoculant combination was applied when compared with recommended dose of fertilizers (inorganic). Among different treatment combinations tried, the most effective treatment was vermicompost + Azospirillum sp. + Glomus sp. (28.94 t ha-1), followed by compost + Azospirillum sp. + Glomus sp. (26.93 t ha-1), as compared to recommended inorganic NPK (24.11 t ha-1). Maximum root colonisation (74%) with microbial inoculants at 180 days after planting was observed with vermicompost + Azospirillum sp. + Glomus sp. Maximum bacterial population (105.25 x 105 CFU g-1 soil) at harvest was noticed in compost + Azospirillum sp. + Glomus sp., as compared to lowest population with recommended NPK (56.35 x 105 CFU g-1 of soil).